2020
DOI: 10.1177/0004867420918659
|View full text |Cite
|
Sign up to set email alerts
|

Inconvenient truths in suicide prevention: Why a Restorative Just Culture should be implemented alongside a Zero Suicide Framework

Abstract: Objective: The prevailing paradigm in suicide prevention continues to contribute to the nihilism regarding the ability to prevent suicides in healthcare settings and a sense of blame following adverse incidents. In this paper, these issues are discussed through the lens of clinicians’ experiences as second victims following a loss of a consumer to suicide, and the lens of health care organisations. Method: We discuss challenges related to the fallacy of risk prediction (erroneous belief that risk screening can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(79 citation statements)
references
References 55 publications
0
67
0
12
Order By: Relevance
“…Researchers have identified that mental health interventions alone were ineffective in reducing suicide rates, rather, it was more important to address major social determinants such as employment and relationship issues (Jorm, 2020). Ongoing critique of the validity of traditional risk stratification algorithms and questions of whether psychiatrists should be expected to predict suicide in patients (Turner, Stapelberg, Sveticic, & Dekker, 2020) relate to this. With ongoing government commitment to funding suicide prevention initiatives, publications on suicide prevention will likely remain high in the coming years.…”
Section: Methodsmentioning
confidence: 99%
“…Researchers have identified that mental health interventions alone were ineffective in reducing suicide rates, rather, it was more important to address major social determinants such as employment and relationship issues (Jorm, 2020). Ongoing critique of the validity of traditional risk stratification algorithms and questions of whether psychiatrists should be expected to predict suicide in patients (Turner, Stapelberg, Sveticic, & Dekker, 2020) relate to this. With ongoing government commitment to funding suicide prevention initiatives, publications on suicide prevention will likely remain high in the coming years.…”
Section: Methodsmentioning
confidence: 99%
“…A review of literature on Just Culture was undertaken, and although initially more traditional approaches to Just Culture (Marx, 2001; Reason, 2016; Wachter and Pronovost, 2009) were considered, a decision was made that Restorative Just Culture (RJC) provided a more compelling way forward. A separate publication outlines learnings about the importance of RJC in the context of ZSF implementation (Turner et al, 2020).…”
Section: Leadershipmentioning
confidence: 99%
“…A new approach to learning from clinical incidents, Gold Coast Clinical Incident Response Framework (GC-CIRF), was developed, which was structured around principles of RJC (including the strong engagement of all stakeholders), human factors, complexity and safety II (GCMHSS 2020a; Turner et al, 2020). The new process also supports enhanced quality and strength of recommendations arising from these reviews.…”
Section: Improvementioning
confidence: 99%
See 1 more Smart Citation
“…Complex psycho-socio-cultural factors impact the aetiology and outcomes of mental disorders and of related concerns such as suicidality. In their recent article, Turner et al (2020) clearly articulate the value of combining the Zero Suicide Framework with principles of a Just Restorative Culture. This article also acknowledges ongoing debates and concerns about the Zero Suicide Movement.…”
mentioning
confidence: 99%